Ethical Theory in German Business Ethics Research - Preuss, Lutz (Journal of business ethics, 1999)
This article offers an overview over the wide scope business ethics has reached in German speaking countries; works which in their majority are not yet available in English translation. The proposed concepts range from a focus on the individual manager and a focus on moral education of managers, via the procedural model of discourse ethics to pressure group ethics and business ethics from a Christian point of view. Other authors suggest an economic theory of moral behaviour, or see ethics as an assurance for decisions under uncertainty or argue for a more enlightened concept of economic rationality.